OBTAINING UREA COMPLEX FERTILIZER WITH PHYSIOLOGICALLY ACTIVE SUBSTANCES - Ibrohimjon Abidov; Farhod Fayzullaevich Hoshimov (Research Focus International Scientific Journal, 2024)
The possibility of obtaining urea with physiologically active substances (PAS) has been studied. The studies used spectrophotometric methods of determination and statistical processing of results. A method for monitoring PAS in the composition of modified urea, as well as a technology for producing fertilizer, has been developed. A developed method for determining PAS in modified urea with an accuracy of at least 0.026%, which makes it possible to control the technological process of large-scale production of modified urea.